2020
DOI: 10.1210/clinem/dgaa359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Potassium or Sodium Supplementation on Mineral Homeostasis: A Controlled Dietary Intervention Study

Abstract: Context Although dietary potassium and sodium intake may influence calcium-phosphate metabolism and bone health, the effects on bone mineral parameters, including fibroblast growth factor 23 (FGF23), are unclear. Objective Here, we investigated the effects of potassium or sodium supplementation on bone mineral parameters. Design, setting, participants We perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 64 publications
2
16
0
Order By: Relevance
“…Yet, the association between urinary potassium excretion and FGF23 was independent of urinary phosphate excretion, as proxy for dietary phosphate intake [26]. Furthermore, current results were in line with a short-term placebo and diet-controlled intervention trial wherein potassium chloride supplementation led to a decrease of FGF23 levels in pre-hypertensive individuals [12]. Similar to the interventional study, participants with higher urinary potassium excretion had a lower fractional phosphate excretion, and a higher TMP/GFR, which are expected findings if FGF23 is directly decreased by potassium [27].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Yet, the association between urinary potassium excretion and FGF23 was independent of urinary phosphate excretion, as proxy for dietary phosphate intake [26]. Furthermore, current results were in line with a short-term placebo and diet-controlled intervention trial wherein potassium chloride supplementation led to a decrease of FGF23 levels in pre-hypertensive individuals [12]. Similar to the interventional study, participants with higher urinary potassium excretion had a lower fractional phosphate excretion, and a higher TMP/GFR, which are expected findings if FGF23 is directly decreased by potassium [27].…”
Section: Discussionsupporting
confidence: 83%
“…Similar to the interventional study, participants with higher urinary potassium excretion had a lower fractional phosphate excretion, and a higher TMP/GFR, which are expected findings if FGF23 is directly decreased by potassium [27]. In contrast, plasma phosphate concentrations did not differ between the urinary potassium excretion sex-specific tertiles, whereas in an intervention study, it was found that plasma phosphate increased after potassium supplementation [12]. This might indicate that the increase of plasma phosphate due to the lowering of FGF23 levels is a short-term effect.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Rat studies have shown that a potassium deficiency can result in phosphaturia ( 38 ). Similarly, in humans, potassium supplementation leads to a decrease in FGF23 and an increase in serum phosphate levels ( 39 ). Hypokalaemia can occur in any patient with CS ( 40 ).…”
Section: Discussionmentioning
confidence: 99%